Challenges and Opportunities of Arts-Based Science Learning Among Basic Level Students amid Covid 19 Pandemic - Acharya, Kamal Prasad; Acharya, Milan; Khatri, Sarswati (Journal of Advanced College of Engineering and Management, 2022)
This paper provides an overview of the emergent practices of arts-based science teaching and learning in public schools in Nepal. It also shares why arts-based science learning has emerged as a shift in teaching and learning from a dogmatic approach to arts-based learning as well as the opportunities and challenges amid COVID 19 pandemic. QUAN qual research method → was applied in this research. The questionnaire survey was used to collect the quantitative data whereas an in-depth interview was taken to collect the qualitative information in this study. 300 students have been selected randomly out of 1300 study population by using the Raosoft sample size calculator with a 95% level of confidence and with a 5% margin error. It is found that the use of figures, posters, soil and sand art, songs and drama promote the understanding of students’ science learning and their achievement score. The findings from this study are expected to encourage the Nepal government, local governments, and public schools to bring local practices into central level policies to transform the dogmatic approach to arts-based teaching and learning.